MyPlate for Dysphagia - Jamila R. Lepore; Nancy J. Gal; Wendy J. Dahl (EDIS)
Resources and tools at ChooseMyPlate.gov that provide clear, actionable information about how to make better food choices can be easily adapted for persons with swallowing difficulties (dysphagia) that require texture-modified foods. This 3-page fact sheet was written by Jamila R. Lepore, Nancy Gal, and Wendy J. Dahl, and published by the UF Department of Food Science and Human Nutrition, December 2012.